What is the way of water meters development – opportunities and threats resulting from electronic water meters usage - Cichoń , Tomasz; Królikowska, Jadwiga (Instal, 2019)
Common and very dynamic development of electronic equipment allowed for remote readings of all types of utility meters. It has also revolutionized the readings technology and changed the way of thinking about meters’ construction. Stepping away from traditional, mechanical meters forces to change the way we evaluate readings’ accurateness. New technologies pose a great challenge for the formal evaluation of meters’ efficiency (legal metrological audit). The article describes additional opportunities created by electronical technologies both for the utility providing companies as well as for their customers. It also describes the threats for media providers and customers in the area of settling transaction disputes.
Keywords: smart water meter; cold/hot water usage